2018
DOI: 10.1111/iej.12893
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the ProTaper retreatment system in removing Thermafil, GuttaCore or vertically compacted gutta‐percha from curved root canals assessed by micro‐CT

Abstract: Remaining filling material and dentine removal were similar for all canal filling techniques. Regaining working length was significantly faster for GuttaCore compared with Thermafil and vertically compacted gutta-percha. Procedural errors occurred during retreatment of severely curved root canals with the ProTaper Universal Retreatment files in 5 of 60 canals (8%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 38 publications
(95 reference statements)
3
22
1
2
Order By: Relevance
“…The statistical analysis of the areas of gutta percha inside the canal after retreatment, shows that Thermafil ® group has a minor number of residues in the apical third compared to the Warm Vertical compaction group and especially to the GuttaCore Pink ® group, although the difference is not statistically significant. This is also in accordance with the paper of 13,15) on the previous GuttaCore ® .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The statistical analysis of the areas of gutta percha inside the canal after retreatment, shows that Thermafil ® group has a minor number of residues in the apical third compared to the Warm Vertical compaction group and especially to the GuttaCore Pink ® group, although the difference is not statistically significant. This is also in accordance with the paper of 13,15) on the previous GuttaCore ® .…”
Section: Discussionsupporting
confidence: 93%
“…In addition, Endal et al 14) pointed out that GuttaCore ® can be removed in less time from root-end cavities than a root filling performed with a cold lateral condensation technique and Rödig et al 15) demonstrated that regaining a working length was significantly quicker with GuttaCore ® when compared with Thermafil ® and vertically-compacted gutta-percha.…”
Section: Introductionmentioning
confidence: 99%
“…, Rödig et al . ). Several previous studies reported the efficacy of reciprocating instruments [Reciproc (VDW, Munich, Germany) and WaveOne] for the retreatment of straight and curved canals, albeit without complete removal of the filling materials (Fruchi et al .…”
Section: Introductionmentioning
confidence: 97%
“…, Rödig et al . , ). The system consists of three instruments (D1, D2 and D3) that have convex and triangular cross section.…”
Section: Introductionmentioning
confidence: 99%
“…The instrument was operated at 100 µA and 65 kV, and 0.013 mm slice thickness with radiation of <1 µSv/h at 10 cm from the instrument surface and reconstruction time of 45 seconds. 2 , 19 …”
Section: Methodsmentioning
confidence: 99%